2014
DOI: 10.1088/0022-3727/47/13/135103
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the optical response in a biodegradable polymer/azo-dye film by the addition of carbon nanotubes

Abstract: A new biodegradable photoresponsive material was developed using poly(lactic acid) (PLA) as the matrix material and Disperse Orange 3 (DO3) as photoisomerizable azo-dye. It was observed that the addition of multi-walled carbon nanotubes (MWCNTs) leads to a new phenomenon consisting of an enhancement of the optical anisotropy in a wide range of temperatures. In particular, the optical anisotropy increases 100% at room temperature. Moreover, the material containing MWCNTs shows a faster optical response that is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 25 publications
4
18
0
Order By: Relevance
“…We have already demonstrated that the incorporation of CNTs enhances some of the optical properties that DO3 confers to the polymer. It was observed that the addition of a small amount of 0.05 wt% of CNTs leads to a new phenomenon consisting of an enhancement of the optical anisotropy [14]. Moreover, diffraction gratings were recorded on the nanocomposites, and it was shown that the CNTs addition lead to increases in the maximum diffraction efficiency as well as the remanent efficiency by 20% [15].…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…We have already demonstrated that the incorporation of CNTs enhances some of the optical properties that DO3 confers to the polymer. It was observed that the addition of a small amount of 0.05 wt% of CNTs leads to a new phenomenon consisting of an enhancement of the optical anisotropy [14]. Moreover, diffraction gratings were recorded on the nanocomposites, and it was shown that the CNTs addition lead to increases in the maximum diffraction efficiency as well as the remanent efficiency by 20% [15].…”
Section: Introductionmentioning
confidence: 98%
“…Covalent and non-covalent functionalizations of carbon nanotubes were proposed in order to have a good dispersion of them in a PLA matrix [5], [8], [13] and [14]. One easy and effective way to obtain this is through a non-covalent functionalization using the azo dye Disperse Orange 3 (DO3), which can interact with PLA [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the previous results, the material with MWCNTs presents a different behavior with respect to the DO3 film reflecting that the presence of MWCNTs plays an important role in the optical response. In fact, the two observations previously mentioned in the description of Figure 3a could be explained in terms of the - interaction between DO3 molecules and MWCNTs [1,4]. This interaction generates that some fraction of DO3 molecules are preferentially in the vicinities of MWCNTs and less molecules are available for photoisomerization and thus for photobleaching.…”
Section: Figurementioning
confidence: 72%
“…Particularly, the electronic structure of carbon nanotubes and azo-dye chromophores allows them to weakly interact via a non-covalent binding [1,2]. Among the many possible ways of working with carbon nanotubes and azo-dye chromophores, one alternative turns out from the addition of both carbon nanotubes and azo-dye molecules into a polymeric matrix [3,4]. As a result, this nanocomposite material can exhibit new properties given by the presence of the dye and the nanotubes.…”
Section: Introductionmentioning
confidence: 99%